A qualitative study on general practitioners’ perspectives on late-life depression in Singapore—part II: system- and physician-related factorsResearch in context - Anna Szücs; V Vien Lee; Laurie J. Goldsmith; Alicia H. Ong; Tim J. Hart; Victor W.K. Loh; Monica Lazarus; Choon Kit Leong; Vivien M.E. Lee; Foon Leng Leong; Doris Young; Andrea B. Maier; et al. (The Lancet Regional Health. Western Pacific)
Summary: Background: Little is known about the practices and resources employed by general practitioners (GPs) in Singapore to manage late-life depression. As the country is stepping up its efforts to promote collaborative care across community mental health and geriatric care, understanding GPs’ current practices when managing late-life depression appears timely. Methods: This qualitative descriptive study explored the perspectives on late-life depression of 28 private GPs practicing in Singapore through online semi-structured group and individual interviews. GPs were purposively sampled across age, gender, and ethnicity. Analysis followed a reflexive thematic approach and focused on physician- and system-related factors. Findings: Clinical instinct, experience, and knowledge of appropriate resources for specific patients played an important role for GPs during late-life depression care. GPs paid particular attention to communicating with patients tactfully during initial assessments and diagnosis, although some GPs chose to be upfront with patients with whom they had already established rapport. Using non-English languages when communicating about depression could mitigate stigma in some cases but added confusion in others. GPs relied primarily on their own professional support network to manage late-life depression. Although GPs acknowledged the usefulness of public care services, they felt that collaborative care was hindered by a lack of efficient communication channels between providers and appropriate financial coverage to coordinate the frequently complex care of depressed older adults. Interpretation: Current resources and practices to manage late-life depression vary greatly between private GPs in Singapore. This needs to be considered during ongoing reforms to achieve effective collaborative care. Funding: This work was funded by the Division of Family Medicine Research Capabilities Building Budget under the project “Technology and Compassion: Improving Patient Outcomes Through Data Analytics and Patients’ Voice in Primary Care” [NUHSRO/2022/049/NUSMed/DFM].